2018
DOI: 10.1186/s12917-018-1543-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-molecular-weight chitosan on the growth performance, intestinal morphology, barrier function, cytokine expression and antioxidant system of weaned piglets

Abstract: BackgroundChitosan was used as an alternative to promote the growth of weaned piglets. And low-molecular-weight chitosan (LC) is one of chitosan derivatives and maintain beneficial biological properties of chitoson. The present experiment was carried out to examine the effects of LC on the growth performance, intestinal morphology, barrier function, cytokine expression, and antioxidant system of weaned piglets.ResultsA total of 40 piglets weaned at 21 d of age, with average body weight 6.37 ± 0.08 kg, were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…LMWC possesses a wide range of biological activities, including anti-inflammatory and immunoregulatory actions [15], making it an attractive candidate for use in food, agricultural and medical industries. A recent study revealed that LMWC supplementation was beneficial to maintaining the intestinal barrier function in pigs after weaning [16]. Nevertheless, no prior information is available concerning the influences of LMWC supplementation on intestinal repair in weaned pigs challenged with ETEC.…”
Section: Introductionmentioning
confidence: 99%
“…LMWC possesses a wide range of biological activities, including anti-inflammatory and immunoregulatory actions [15], making it an attractive candidate for use in food, agricultural and medical industries. A recent study revealed that LMWC supplementation was beneficial to maintaining the intestinal barrier function in pigs after weaning [16]. Nevertheless, no prior information is available concerning the influences of LMWC supplementation on intestinal repair in weaned pigs challenged with ETEC.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that heat stress can induce multiple physiological disturbances, including endocrine disorders [3,4], electrolyte imbalance [5], immune dysfunction [6][7][8], and oxidative stress [9][10][11]. The heat stress response pathway is partly attributed to the increase of pro-inflammatory cytokines and reactive oxygen species (ROS) production [12][13][14]. The increased ROS resulted in stimulated intracellular and extracellular superoxide formation and was responsible for oxidative stress [15].…”
Section: Introductionmentioning
confidence: 99%
“…•Na 2 in sows modulated immune responsivity by inhibiting the expression of pro-inflammatory cytokines in weaned piglets. Hu et al[41] reported that dietary supplementation with 50 mg/kg low-molecularweight chitosan which has antioxidant activity significantly reduced the jejunal mucosal expression of pro-inflammatory cytokines. Yin et al suggested that the concentrations of IFN-γ, IL-1β and IL-2 were decreased in pigs as the PQQ•Na 2 supplementation was increased and this is consistent with our study results[22].Parenteral nutrition can be useful to prevent and reverse malnutrition and to maintain the nutritional status of patients who are unable to receive adequate enteral nutrition.…”
mentioning
confidence: 99%